América Central: Cambio y continuidad en el proceso de consolidación democrática (2004-2008) - Avila, Carlos Federico Domínguez (Diálogos Latinoamericanos, 2008)
The paper explores the recent presidential electoral processes being held in Central American countries since 2004. The electoral processes suggest a shift toward center and left wing governments. Also some scenarios and perspectives are mentioned in the democratic consolidation of the isthmus countries.